4
$\begingroup$

Second order linear differential equation is given below.

$y''+\frac{2}{x}y'+k^2y=0,$

where $k$ is constant and $x\neq 0$

I already know that the basis are $y_1=\frac{e^{-ikx}}{x}$ and $y_2=\frac{e^{ikx}}{x}$. (from book)

But i don't know how to find the basis of that ODE...

$\endgroup$
2
  • $\begingroup$ So... Do you want a method to find two independent solutions of this ODE? $\endgroup$ – user228113 Jun 24 '15 at 12:53
  • $\begingroup$ let $y=e^{rx}$ and after substitution in :$y''+\frac{2}{x}y'+k^2y=0,$ we get: $r²e^{rx}+\frac{2}{x}re^{rx}+k²e^{rx}=e^{rx}(r²+\frac{2}{x}r+k²)=0$ may this substistion will work .try it out $\endgroup$ – Zeraoulia rafik Jun 24 '15 at 14:19
1
$\begingroup$

$$xy''+2y'=-k^2xy$$ $(xy)'=xy'+y$

$(xy)''=(xy''+y')+y'=xy''+2y'$

$$(xy)''=-k^2(xy)$$ This is the wellknown ODE $\quad Y''=-k^2Y \quad\to\quad Y=c_1\cos(kx)+c_2\sin(kx)$ $$xy=c_1\cos(kx)+c_2\sin(kx)$$ $$y=c_1\frac{\cos(kx)}{x}+c_2\frac{\sin(kx)}{x}$$

$\endgroup$
1
$\begingroup$

You may reduce the given DE into another with first derivative removed as follows:

$1$.Put $y=u(x)v(x)$ in the given DE

$2$.Equate the coefficient of $v'(x)$ to zero to obtain $u(x)$.

$3$. Now solve the reduced DE for $v(x)$ with its first derivative term missing by usual methods of CF and PI.

$4$.The solution is $y(x)=u(x)v(x)$.

$\endgroup$
1
  • $\begingroup$ ok. I solved the problem from your idea. Thanks! $\endgroup$ – Donghee Park Jun 25 '15 at 4:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.